The gas chromatography of ammonia : heterogeneous systems containing silver ammines - Rutenberg, Aaron Louis (Department of Chemistry, 2016)
The gas-liquid chromatography of ammonia on fixed phases consisting of silver salts dissolved in high boiling organic liquids, yielded chromatograms showing a peak followed by a plateau or plateaux of decreasing height. This phenomenon was ascribed by du Plessis to the formation of solid ammine complexes; the plateau height being some function of the dissociation pressure of the complex. Calibration of the detector response to ammonia enabled the dissociation pressures of the complexes to be computed from the plateau heights. Certain silver salt-solvent systems gave chromatograms, whose plateaux showed decay of the rear-end, or whose heights divided into two levels. This was attributed to rate-effects caused by slow decomposition of the complex. Kinetic considerations and phase rule interpretation of the plateau portion of the chromatogram, yielded quantitative information about the complexes, while the investigation of temperature effects I gave a measure of the bond strength between the ammonia and silver. A modified tensimetric experiment gave results supporting the quantitative information derived from the chromatograms. Freshly prepared columns absorbed ammonia due to the formation of a solid complex, whose dissociation pressure lay below the limits of the detector response. The ratio of the absorbed ammonia to the amount of silver in the column gave the apparent molar composition of the complex. The work described in this thesis has shown that the chromatographic flow system affects the apparent values of the thermodynamic quantities associated with the complexes, and this has been accounted for. This work also showed that the process underlying solid complex formation in the liquid phase is the same as for homogeneous complex formation in the liquid phase, which has been reported in the literature. The appearance of a plateau in the case of solid complexes is due to an invariant state prevailing under constant temperature conditions, since the number of phases formed is sufficient to yield this state, and hence define the pressure variable. The information obtained from the literature, enabled an alternative chromatographic method of investigating solid ammine complexes to be proposed for future work. Finally the chromatography of ammonia on the toluidine isomers as liquid substrates was carried out in order to investigate possible hydrogen bonding effects.